Performance evaluation of cross-layer opportunistic MAC/routing with node's mobility for wireless body area networks - Awang, A. (Institute of Electrical and Electronics Engineers Inc., 2016)
Wireless Body Area Networks (WBANs) offer many new promising applications in the area of remote health monitoring. In WBANs, sensor nodes deployed on a human body often exhibit high mobility patterns due to body posture movement. In a prior work, a Cross-layer Opportunistic MAC/Routing (COMR) protocol has been proposed for multi-hop WBAN but the evaluation was made using a static network topology. As an extension, in this work the performance of COMR protocol is investigated taking into account node's mobility with different speeds depending on body positions. The impacts of varying payload sizes are evaluated for both COMR and Simple Opportunistic Routing (SOR) protocols using a mobility model in two scenarios: standing and walking. Simulation results exhibit that COMR performs better than SOR in terms of reliability, network lifetime, end-to-end (ETE) delay and energy efficiency. Â© 2015 IEEE.